Розробка алгоритму формування просторових монотонних кривих - Гавриленко, Євген Андрійович; Холодняк, Юлія Володимирівна; Тетервак, Ілля Романович; Havrylenko, Yevhen; Kholodniak, Yuliia; Tetervak, Illia (Запоріжжя : ТДАТУ, Видавничий дім «Гельветика», 2025)
UA: Формування поверхонь заданих масивом точок є актуальним завданням геометричного моделювання. Модель поверхні формується на основі лінійного каркаса, елементи якого інтерполюють послідовності точок. Контроль наявності особливих точок у ліній каркаса є важливою умовою для забезпечення необхідних властивостей поверхні. Контроль наявності особливих точок у кривої, яка інтерполює точковий ряд, засновано на відмові від її аналітичного представлення. Крива формується у вигляді області можливого розташування її монотонних частин. Як лінійний елемент каркаса використовується обвід, що формується всередині області можливого розташування частин інтерполюючої кривої. Алгоритм моделювання просторових елементів каркаса засновано на формуванні допоміжних плоских дискретно представлених кривих, які визначають конфігурацію та властивості просторових обводів. На основі запропонованого алгоритму розроблено програмне забезпечення для автоматизованого формування обводів в CAD-системі. EN: The formation of complex functional surfaces given by an array of points is an urgent task of geometric modeling. The geometric model of the surface is formed on the basis of a discrete linear framework, the elements of which are curved lines that interpolate sequences of points selected from the original array. Controlling the presence of singular points in the framework lines is an important condition for ensuring the necessary surface properties. The work solves the problem of modeling a smooth contour of the interpolating point series belonging to the curve line that contains the minimum number of singular points under the conditions of the problem. The solution of the problem of controlling the presence of singular points in the curve that interpolates the given point series is based on the rejection of its analytical representation. The interpolating curve is formed in the form of a region of possible location of its monotonic parts. All curved lines that meet the conditions of the problem cannot be located outside the specified region. As a linear element of the frame, a contour is used, which is formed inside the region of possible location of parts of the interpolating curve, along which the curvature values monotonically increase or decrease. The absolute error of interpolation of the point series is estimated by the width of the specified region. If the interpolation error of the original point series turns out to be greater than the assigned value, then the width of the region of the curve location is reduced by assigning intermediate points. The algorithm proposed in the work for modeling spatial linear elements of the frame while controlling the occurrence of special points is based on the formation of auxiliary flat discretely represented curves, the characteristics of which determine the configuration and properties of spatial contours. Based on the proposed algorithm, software has been developed for the automated formation in the CAD system of contours representing curved lines from the surface determinant.
Development of an algorithm for forming spatial monotone curves
Keywords: монотонна крива; стичне коло; прилегла площина; область розташування кривої; обвід; алгоритм; програмне забезпечення; monotone curve; tangent circle; adjacent plane; region of the curve; contour; algorithm; software